Efficacy of botanicals extracts against Spodoptera litura (Lepidoptera: Noctuidae) under laboratory condition - Safder, Arfa; Afzal, Zohaib; Munawar, Fizza; Hashmi, Ahad Masood; Ali, Rafia Bakht; Amanat, Nagina (Journal of Scientific Agriculture, 2022)
Numerous cultivated plants are attacked by Spodoptera litura, which also significantly reduces crop yields. In this study, a green strategy was used to assess the toxicological impact of three plant extracts (Eucalyptus globulus, Allium sativum, and Azadirachta indica) against S. litura larvae in their second and third instars. The study resulted that among the tested extracts, neem (A. indica) was found to be the most toxic and efficient extract followed by E. globulus and A. sativum. 29.92, 56.61, and 79.53% mortality of 2nd instar larvae were recorded at 3, 5, and 7 ppm, respectively, while 24.52, 27.66, and 72.42% of 3rd instars. Among the tested extracts, A. sativum was the least toxic extract than others. One of the main causes of large losses in field crops is insect pest damage. According to the study’s findings, A. indica extract has the potential to lessen S. litura damage to crops as a natural substitute for chemical pesticides without harming beneficial species.